'At least I have done something': A qualitative study of women's social egg freezing experiences. (December 2022) - De Proost, Michiel; Coene, Gily; Nekkebroeck, Julie; Provoost, Veerle
Social egg freezing has become an expanding clinical practice and there is a growing body of empirical literature on women's attitudes and the sociocultural implications of this phenomenon. Yet, its impact remains subject to ethical controversy. This article reports on a qualitative study, drawing on 18 interviews with women who had elected to initiate at least one egg freezing cycle in Belgium. Our findings, facilitated by a 'symbiotic empirical ethics' approach, shed light on the concerns and perceptions that accompany women's decisions while supporting a more context-sensitive reading of the ethical debate. We identified three key themes: feeling overwhelmed with uncertainty and a threatening future, bodily discomfort and distress during the medical process, and the endless pursuit of peace of mind. One of the issues that emerges from these findings is the risk ritual function of social egg freezing, referring to routine actions of risk anticipation that mitigate uncertainty and express a sense of individual responsibility. While more research is needed, this conceptualisation provides a starting point to flesh out the wider context of this moral practice and its symbolic meaning for women.